Studi Rencana Penentuan Halte Sistem Angkutan Umum Massal Berbasis Jalan Pada Koridor 6 Di Kabupaten Bogor (Ciawi-Cisarua) - Ade Nirwan; Rulhendri; Tedy Murtedjo (Indonesian Society of Applied Science, 2026)
The mass public transportation system (SAUM) is one of the Bogor Regency Government's efforts to alleviate existing traffic congestion and provide people with alternative transportation options. Based on the study, six main corridors have been identified for development, one of which is Corridor 6, specifically from Ciawi to Cisarua. The purpose of this study is to determine the number and location of bus stops to meet potential demand and estimate the potential demand from each stop point. The analytical method used is the analytical descriptive research method of the Ministry of Land Transportation's equations. The results of the research that have been carried out have obtained 17 stopping points that can meet potential demand on the Corridor 6 route, with the locations of Ciawi Hospital Stop, Ciawi Gas Station Stop, Gadog Stop, Hermina Hospital Stop, Pasir Angin Stop, GPIB Nehemia Stop, Cibogo Gas Station Stop, SMK YMA Megamendung Stop, RM Ma Pirah Stop, Cimori Riverside Stop, Taman Wisata Matahari Stop, MAN 1 Cisarua Stop, Parama Hotel Stop, Cibulan Clinic Stop, Taman Safari Stop (RSPARU), Taman Safari 1 Stop, and SDN Cibeureum Stop.